ANALYSIS OF THE CHARACTERISTICS OF COFFEE SHOP VISITORS ON PERCEPTIONS, KNOWLEDGE AND ATTITUDES OF COVID-19 TRANSMISSION IN BANDA ACEH - Riansyah, Ferdi; Saputra, Mahruri; Putra, Eridha (Aceh Sanitation Journal, 2023)
Background: Corona Virus is a large family of viruses that are known to cause serious lung diseases, including the Middle East Respiratory Syndrome (MERS-). and the attitude of the spread of covid-19 in Banda Aceh City. Methods: This study was conducted using a quasi-questionnaire, with the Quantitative Analytical Method, with a cross sectional approach. The population in this study were visitors at 51 a coffee shop in the city of banda aceh, with inclusion criteria >17 years, did not do take away with exclusion criteria below <17 and take away with a sample of 264 people. Data collection was carried out by direct questionnaire, where this questionnaire had been tested for validity and reliability with cronbath alpha 0.709 tested on 20 people. The independent variable is the characteristics of coffee shop visitors and the dependent variable is the perception, knowledge and attitude of the spread of covid-19. The analysis carried out is the square test. This research has received approval from the Research Ethics Committee of the Faculty of Medicine, Syiah Kuala University RSUDZA with No: 067/EA/FK-RSUDZA/2021. Results: Chi square test showed that there was a relationship between the characteristics of coffee shop visitors Last Education with perception (p value = 0.002), knowledge (p value = 0.000), attitude (p value = 0.000), Work with knowledge (p value = 0.049), and Residence with attitude (p value = 0.040) the spread of covid-19 in Banda Aceh City. The results of the Chi square test also obtained a non-significant value between age and perception (p value = 0.160), knowledge (p value = 0.059), attitude (p value = 0.262), between gender and perception (p value = 0.148), knowledge (p value = 0.182), attitude (p value = 0.065), between work and perception (p value = 0.147), attitude (p value = 0.207), between residence and perception (p value = 0.481), knowledge (p value = 0.240), the spread of covid-19 in Banda Aceh City. Conclusion: There is a relationship between the characteristics of the last education with perceptions, knowledge and attitudes, work with knowledge and residence with attitudes. There is no relationship between age characteristics with perceptions, knowledge and attitudes, gender with perceptions Knowledge and attitudes, work with perceptions and attitudes, residence with perceptions and knowledge of the spread of covid 19 in Banda Aceh City.